Landscape Design of University Campuses and User Satisfaction - Deniz Gozde Ertin Tezgor; Beste Karakaya Aytin (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
University campus gardens provide the integrity of the environment with educational buildings, connect the users and buildings, and provide liveable spaces for users. Campuses serve as a public space for academic, administrative and technical staff, especially students, as well as incoming visitors. As a public space, the ability of students to meet all their recreational, social and cultural needs is directly related to the content and designs of the open and green spaces of the campuses. It is essential to ensure the landscape designs of these spaces, in line with the structural and planting design principles, and with the successful composition of the user-space relationship where the user needs and desires are determined. From this point of view, it is aimed to evaluate the landscape designs of the two campuses of Trakya University, where art and design-oriented education is realised, in terms of user satisfaction. For this purpose, it was revealed by a survey that measures the satisfaction of the users of the two campuses where determined the spatial and landscape requirements of design-based education. In the survey, the users' duration and purpose of use of the campus, feelings created by various equipment on users.